Pengaruh Pendidikan Kewirausahaan dan Kreativitas Terhadap Intensi Berwirausaha Melalui Self-Efficacy Sebagai Variabel Mediasi pada Santri Ahsanul ’Ibad - Putri Solehah; Agus Wibowo; Ari Saptono (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
This study aims to determine the effect of entrepreneurship education and creativity on entrepreneurial intention through self-efficacy as a mediating variable among students at Pondok Pesantren Ahsanul 'Ibad. This research applies a quantitative approach with a survey method. The population in this study was 250 students, and a sample of 154 respondents was selected using simple random sampling based on the Slovin formula. Data collection was carried out through paper-based questionnaires with a five-point Likert scale. Data analysis used Structural Equation Modeling-Partial Least Squares (SEM-PLS) assisted by SmartPLS 4 software. The results showed that entrepreneurship education and creativity have a positive and significant direct effect on entrepreneurial intention. Furthermore, entrepreneurship education and creativity also have a significant direct effect on self-efficacy, and self-efficacy directly affects entrepreneurial intention. The mediation analysis proves that self-efficacy partially mediates the relationship between entrepreneurship education and creativity on entrepreneurial intention. This indicates that a high level of entrepreneurship knowledge and creativity will significantly foster entrepreneurial intention when driven by strong individual self-confidence.